Necessary changes in school direction. (Journal of Parents and Teachers, 2014)
None currently doubts about the relevance of Headmasters as revitalizing elements of school life, nevertheless the method through which the headmaster gets his position, the qualifications he possesses and the acquired compromises condition his work. The changes established by the LOE give more organizational autonomy with which develop a shared vision of future to achieve the common goals; develop integrating, motivating and facilitating leadership; identify the necessary competences to get the pursued goals and the organizational changes to permit a bigger satisfaction in users.
Keywords: general didactics; school organization; school direction; LOE; school council; staff meeting; teaching coordination organs